BPK RI Audit Quality in Ethical Perspective - Tazkiyah Mutiara Rahma; Tiara Setra Linuhung; Novika Rahmadisa; Lies Azizah; Alfianda Kurniawan; Chelvin Nata Wijaya; Raden Rizka Aulya (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: The purpose of this study is to see the influence of an ethical perspective of an audit quality. Research Methodology: This study uses a descriptive analysis method by collecting the results of previous studies that are relevant to the factors that affect audit quality in an ethical perspective. The data collection begins by looking for literature on previous research related to the Effect of Ethics on BPK RI's Audit Quality with the keywords Factors Affecting Audit Quality and Professional Ethics. The literature search process uses Google Schoolar and Publish or Perish. Result: The findings obtained from the articles obtained indicate that there is a relationship between ethical perspective and audit quality. Limitations: This study has limitations in terms of the scope of research that only focuses on individual ethics. The scope of ethics is very broad and is not only influenced by things that come from the individual, but can also be influenced by environmental factors and other things. Contribution: This study can provide benefits regarding how important individual ethical factors are to produce audit quality.